Failure modes, mechanisms and effect analysis on temperature redundant sensor stage. (December 2018) - Catelani, M.; Ciani, L.; Venzi, M.
Highlights: This paper focuses on a new approach given by the combination of FMECA and FMMEA. This approach ensures a more detailed analysis and a suitable maintenance policies. A case study on Oil&Gas application is discussed to validate the proposed method. Abstract: This paper focuses on failure analysis using two techniques developed from Failure Mode and Effect Analysis (FMEA), one of the most used methodologies to determine causes and consequences of failures: Failure Mode, Effect and Criticality Analysis (FMECA) and Failure Modes, Mechanisms and Effect Analysis (FMMEA). In this paper their combination is shown to optimize the benefits of both and overcome their drawbacks. This approach ensures high efficiency throughout equipment design and guarantees suitable maintenance policies. It has been applied in a redundant architecture based on temperature sensors included in a Safety Instrumented System for Oil&Gas application.